Analyze the Stereotypes in the Movie Zootopia and How to Eliminate the Typical Stereotypes in Today’s Workplace - Qichao Hao (Studies in Social Science & Humanities, 2023)
After Lippmann put forward the concept of stereotype, people gradually pay attention to the ubiquitous stereotype. In today’s workplace, stereotypes are even more pronounced, especially for women and people with disabilities. By taking Zootopia as an example, this paper aims to analyze the problem of stereotypes in the movie, and put forward some feasible suggestions for eliminating stereotypes based on specific cases.